PKM KELOMPOK KERJA GURU SD KECAMATAN GARUNG KABUPATEN WONOSOBO DALAM MENINGKATKAN KEMAMPUAN GURU DALAM MENCIPTAKAN GAME EDUKATIF BERBASIS SCRATCH - Firdaus Firdaus; Muhtar Sofwan Hidayat; Eli Trisnowati; Alviana Maya Sabilla; Firman Ade Purnomo; Dendi Nur Ahmad (As-Sidanah, 2024)
The 21st century requires everyone to adapt to digital culture. Computational thinking skills help deal with digital culture. These skills can be provided to students through teaching and learning. However, there are several obstacles to achieving this goal. First, teachers do not yet understand how to teach students computing skills through classroom learning. Second, there needs to be more teaching skills based on computational thinking. This community service aims to improve teachers' abilities in training students' computational thinking skills. This is done in the context of teaching and learning to provide 21st-century skills through Scratch programming. The approach used in this activity is educational and participatory. Namely, the implementation of the service contains educational elements and is oriented towards efforts to improve the role of teachers. Community service is carried out through three stages: material preparation, program implementation, evaluation, and monitoring. The material preparation stage involves collecting material from various literature. The program implementation stage provides material regarding 21st-century learning and learning design using Scratch programming. Teachers are also engaged in using Scratch and how to involve students with this programming. The monitoring and evaluation stage includes process evaluation at the end of each activity and product evaluation. This community service shows that 91% of all teachers experienced increased skills in making various learning creations such as animations, games, and simulations based on Scratch programming. Additionally, 87% of all teachers who participated in the activity experienced increased skills in integrating scratch-based teaching materials into learning. This service activity aims to increase teacher skills in teaching computational thinking through scratch programming, which is expected to improve the quality of education in the digital era significantly.